Regulating Environmental and Safety Hazards of Agricultural Biotechnology for a Sustainable World - George Van Cleve (Washington University Journal of Law & Policy, 2002)
This Essay first presents an overview of key legal principles that support sustainability. This Essay then reviews the major alleged risks of agricultural biotechnology. It then describes the existing U.S. and European agricultural biotechnology regulatory system designed to control those risks. Next, this Essay analyzes the existing U.S. regulatory system using sustainability principles. In the course of that analysis, this Essay considers lessons to be derived from three case studies: the permitting of Starlink™ corn, the discovery of Mexican maize containing genetically engineered corn genes, and the possible permitting of transgenic salmon for ocean fish farming. This Essay also considers lessons from the broader regulatory history of pest-protected plants. Based on the analysis of sustainability issues related to agricultural biotechnology, this Essay concludes that despite the obvious, substantial benefits that agricultural biotechnology can confer on society, the United States needs to improve its regulatory process to ensure a proper weighing of the full social benefits and costs of agricultural biotechnology and to clarify liability rules governing the use of agricultural biotechnology. These reforms should provide both better public protection and increased public support for the agricultural biotechnology industry.
Keywords: Sustainable development; Genetically modified foods; Agricultural biotechnology; Environmental protection; International; United States